Intravenous versus inhalational maintenance of anaesthesia for postoperative cognitive outcomes in elderly people undergoing non-cardiac surgery - Miller, David; Lewis, Sharon R; Pritchard, Michael W; Schofield-Robinson, Oliver J; Shelton, Cliff L; Alderson, Phil; Smith, Andrew F (Cochrane database of systematic reviews, 2018)
The use of anaesthetics in the elderly surgical population (more than 60 years of age) is increasing. Postoperative delirium, an acute condition characterized by reduced awareness of the environment and a disturbance in attention, typically occurs between 24 and 72 hours after surgery and can affect up to 60% of elderly surgical patients. Postoperative cognitive dysfunction (POCD) is a new-onset of cognitive impairment which may persist for weeks or months after surgery.Traditionally, surgical anaesthesia has been maintained with inhalational agents. End-tidal concentrations require adjustment to balance the risks of accidental awareness and excessive dosing in elderly people. As an alternative, propofol-based total intravenous anaesthesia (TIVA) offers a more rapid recovery and reduces postoperative nausea and vomiting. Using TIVA with a target controlled infusion (TCI) allows plasma and effect-site concentrations to be calculated using an algorithm based on age, gender, weight and height of the patient.TIVA is a viable alternative to inhalational maintenance agents for surgical anaesthesia in elderly people. However, in terms of postoperative cognitive outcomes, the optimal technique is unknown. To compare maintenance of general anaesthesia for elderly people undergoing non-cardiac surgery using propofol-based TIVA or inhalational anaesthesia on postoperative cognitive function, mortality, risk of hypotension, length of stay in the postanaesthesia care unit (PACU), and hospital stay. We searched the Cochrane Central Register of Controlled Trials (CENTRAL; 2017, Issue 11), MEDLINE (1946 to November 2017), Embase (1974 to November 2017), PsycINFO (1887 to November 2017). We searched clinical trials registers for ongoing studies, and conducted backward and forward citation searching of relevant articles. We included randomized controlled trials (RCTs) with participants over 60 years of age scheduled for non-cardiac surgery under general anaesthesia. We planned to also include quasi-randomized trials. We compared maintenance of anaesthesia with propofol-based TIVA versus inhalational maintenance of anaesthesia. Two review authors independently assessed studies for inclusion, extracted data, assessed risk of bias, and synthesized findings. We included 28 RCTs with 4507 randomized participants undergoing different types of surgery (predominantly cardiovascular, laparoscopic, abdominal, orthopaedic and ophthalmic procedures). We found no quasi-randomized trials. Four studies are awaiting classification because we had insufficient information to assess eligibility.All studies compared maintenance with propofol-based TIVA versus inhalational maintenance of anaesthesia. Six studies were multi-arm and included additional TIVA groups, additional inhalational maintenance or both. Inhalational maintenance agents included sevoflurane (19 studies), isoflurane (eight studies), and desflurane (three studies), and was not specified in one study (reported as an abstract). Some studies also reported use of epidural analgesia/anaesthesia, fentanyl and remifentanil.We found insufficient reporting of randomization methods in many studies and all studies were at high risk of performance bias because it was not feasible to blind anaesthetists to study groups. Thirteen studies described blinding of outcome assessors. Three studies had a high of risk of attrition bias, and we noted differences in the use of analgesics between groups in six studies, and differences in baseline characteristics in five studies. Few studies reported clinical trials registration, which prevented assessment of risk of selective reporting bias.We found no evidence of a difference in incidences of postoperative delirium according to type of anaesthetic maintenance agents (odds ratio (OR) 0.59, 95% confidence interval (CI) 0.15 to 2.26; 321 participants; five studies; very low-certainty evidence); we noted during sensitivity analysis that using different time points in one study may influence direction of this result. Thirteen studies (3215 participants) reported POCD, and of these, six studies reported data that could not be pooled; we noted no difference in scores of POCD in four of these and in one study, data were at a time point incomparable to other studies. We excluded one large study from meta-analysis because study investigators had used non-standard anaesthetic management and this study was not methodologically comparable to other studies. We combined data for seven studies and found low-certainty evidence that TIVA may reduce POCD (OR 0.52, 95% CI 0.31 to 0.87; 869 participants).We found no evidence of a difference in mortality at 30 days (OR 1.21, 95% CI 0.33 to 4.45; 271 participants; three studies; very low-certainty evidence). Twelve studies reported intraoperative hypotension. We did not perform meta-analysis for 11 studies for this outcome. We noted visual inconsistencies in these data, which may be explained by possible variation in clinical management and medication used to manage hypotension in each study (downgraded to low-certainty evidence); one study reported data in a format that could not be combined and we noted little or no difference between groups in intraoperative hypotension for this study. Eight studies reported length of stay in the PACU, and we did not perform meta-analysis for seven studies. We noted visual inconsistencies in these data, which may be explained by possible differences in definition of time points for this outcome (downgraded to very low-certainty evidence); data were unclearly reported in one study. We found no evidence of a difference in length of hospital stay according to type of anaesthetic maintenance agent (mean difference (MD) 0 days, 95% CI -1.32 to 1.32; 175 participants; four studies; very low-certainty evidence).We used the GRADE approach to downgrade the certainty of the evidence for each outcome. Reasons for downgrading included: study limitations, because some included studies insufficiently reported randomization methods, had high attrition bias, or high risk of selective reporting bias; imprecision, because we found few studies; inconsistency, because we noted heterogeneity across studies. We are uncertain whether maintenance with propofol-based TIVA or with inhalational agents affect incidences of postoperative delirium, mortality, or length of hospital stay because certainty of the evidence was very low. We found low-certainty evidence that maintenance with propofol-based TIVA may reduce POCD. We were unable to perform meta-analysis for intraoperative hypotension or length of stay in the PACU because of heterogeneity between studies. We identified 11 ongoing studies from clinical trials register searches; inclusion of these studies in future review updates may provide more certainty for the review outcomes.